(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Virtual learning is the only solution that can be implemented to replace the face-to-face learning process during the Covid-19 pandemic. Several studies have proven that learning with virtual classes can affect the learning outcomes of elementary school students. The purpose of this study was to analyze the effectiveness of the virtual classroom implemented for elementary school students. This type of research is descriptive qualitative with a literature review method (library study). 9 national journals from previous research have been selected based on the criteria that they have been published on the Google Schoolar page in the range of 2020-2021 with a focus on problems regarding virtual classes for elementary school students. The analysis and review process uses a synthetic matrix. The results showed that virtual learning was effective for elementary school students when using learning applications that were mastered by each student, there were agreed learning procedures and rules, supervisory synergy between teachers and parents, and videos and teaching materials were distributed to each. each student. Therefore, it is necessary to have a virtual learning evaluation for elementary school students at least every Sunday, so that students’ difficulties can be known by the teacher and immediately followed up.